Trade-offs in AI assistant choice: Do consumers prioritize transparency and sustainability over AI assistant performance? - Tomohiro Ioku; Jaehyun Song; Eiichiro Watamura (Big Data & Society)
As artificial intelligence (AI) becomes more integrated into society, concerns have arisen about unintended biases in AI-driven decision-making and the environmental impact of AI technology development. AI assistants such as Siri and Alexa, while helpful, can obscure decision-making and contribute to increased energy use and CO2 emissions. The present study explores whether consumers prioritize transparency and environmental sustainability over performance when choosing AI assistants with conjoint designs. Japanese participants were presented with different AI assistant profiles, varying in performance quality, transparency, cost, and environmental efficiency. The results revealed that Japanese participants prioritized transparency over performance when choosing AI assistants, but they prioritized performance over environmental sustainability. Moreover, future-oriented participants placed more importance on sustainability than those with a present orientation, while participants with an internal locus of control valued transparency more than those with an external locus of control. The findings of this study enhance our understanding of how consumers choose AI options and offer valuable guidance for creating AI systems and communication strategies that work effectively.